Management of soils to conserve moisture - Cudney, Everet William (My University, 1907)
Introduction: No other phase of modern farming, unless it be the ever pressing problem of how to keep up the fertility of the soil, is receiving the attention that is given to the problem of conserving the soil moisture. Even in the districts where rainfall is sufficient and where some of the moisture has to be drained away by artificial means there are dry periods which will prevent a maximum yield of any crop unless some measures adopted to save the water not so removed. It is impossible to estimate the loss, in reduced yield of crops, due to the lack of sufficient moisture at the right time. This refers not only to the great droughts in our semiarid regions and to the local droughts which a re likely to occur in any region but also to the unnoticed dryness which comes at a critical time during the growing period of a crop and reduces the yield more or less. When we consider the fact that on a large portion of the cultivated land in the United States there is sufficient moisture precipitated to mature double the average yield of most of the main crops, we see the importance of attempting to save it.
Citation: Cudney, Everet William. Management of soils to conserve moisture. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: Soils; Soils Management; Moisture Conservation; Theses